Trade Openness and China's Economic Development, 1st edition - Yu, Miaojie (Routledge, 2020)
With the expansion of globalization, international trade has played an increasingly significant role, especially for developing countries. As the largest developing country, China has made a lot of efforts to integrate to the global market since its Open and Reform Policy in 1978 and has become the second largest economy in world. So what is the effect of China’s trade-oriented strategy for the country and the world? How did it improve the country’s economic development? These are some critical questions this book discusses.